PROFESSIONAL EDUCATION QUALITY DEVELOPMENT AND ITS ASSESSMENT IN COMPETENCE-BASED MODEL OF LEARNING - Irina N. Emelyanova (Obrazovanie i Nauka, 2015)
The paper deals with the problem of professional education assessment that has become more serious due to competence-based model of learning implementation in higher professional education. The purpose of the article is to reveal the contradictions occurred while implementing competence-based model of learning in higher professional education, and justify rationale for professional training improvement in accordance with professional and federal state educational standards. Methods. The methods involve: the comparative analysis – to study educational occupational standards and federal state educational standards on pedagogical education; and prognostic analysis – to study the analysis of development of a modern educational situation. Results. The basic problem aspects of education quality assessment of modern vocational training are formulated. The study has revealed the following contradictions: a) in occupational and federal state educational standards; b) in educational matters approaching the career conditions and occupational behaviour pattern development mechanism, and real-time correction of occupational behaviour pattern; c) in main educational programs thematic structuring and meta-concreteness of competences content; d) in education quality improvement requirements and lack of clear quality criteria; e) in new teaching techniques and teachers’ readiness to work with them. The contradictions mentioned require some new resources for their adjustment. Scientific novelty. The research findings include a verification and explanation of the professional education idea and mechanism based on professional behaviour pattern and focused on gradual professional socialization. Some ways of professional education formation and quality improvement are suggested. They involve the mechanisms of coordination at all stages of professional training: occupational standards and educational standards development, main educational programmes and curriculum designing, and professional training quality assessment development. Practical significance. The practically tested method of competence assessment while using some interactive methods of teaching and assessing is given in the article. Quality-quantity assessment table containing indices and its assessment criteria is presented in the given article. The author points out the drawbacks of the proposed technique that require a further work and development of measure procedure of specialist training quality.